Target Tokyo Jimmy Doolittle and the raid that avenged Pearl Harbor - Scott, James (James M.) (New York W. W. Norton and Company, 2016)
"On April 18, 1942, sixteen U.S. Army bombers under the command of daredevil pilot Jimmy Doolittle lifted off from the deck of the USS Hornet on a one-way mission to pummel Japan's factories, refineries, and dockyards in retaliation for the attack on Pearl Harbor. The raid buoyed America's morale, and prompted an ill-fated Japanese attempt to seize Midway that turned the tide of the war. But it came at a horrific cost: an estimated 250,000 Chinese died in retaliation by the Japanese. Deeply researched and brilliantly written, Target Tokyo has been hailed as the definitive account of one of America's most daring military operations." -- From the back cover.
Includes bibliographical references (pages 613-622) and index.
Keywords: Doolittle, James Harold -- 1896-1993.; World War, 1939-1945 -- Aerial operations, American; Tokyo (Japan) -- History -- Bombardment, 1942.